Financial Performance Ratios and Financial Distress: CS-ARDL Panel Analysis - Nur Rachmah Wahidah; Dean Herdesviana; Noor Arida Sofiana; Nandan Limakrisna (Penerbit Goodwood, 2026)
Purpose: This study analyzes the influence of Financial Performance, Efficiency, Asset Quality, Capital Adequacy, Liquidity, and Foreign Exchange Exposure on Financial Distress in Islamic financial institutions across major Islamic countries.Methodology: A quantitative approach with panel data analysis was employed using secondary data from institutions in nine countries. The CS-ARDL technique was used to examine the short- and long-term relationships. Findings: Financial Performance, Capital Adequacy, and Liquidity have a significant negative effect on Financial Distress. In contrast, poorer Efficiency, Asset Quality, and Foreign Exchange Exposure significantly increase Financial Distress. The analysis confirms rapid adjustment to long-run equilibrium. Conclusion: This study finds that Financial Performance, Capital Adequacy, and Liquidity reduce financial distress, while Efficiency, Asset Quality, and Foreign Exchange Exposure increase it. Institutions quickly adjust to a long-run equilibrium. This study provides insights for managers and regulators and validates Financial Distress Theory in Islamic finance. However, its focus on major jurisdictions and the lack of macroeconomic factors suggest areas for further research. Limitations: The focus on major jurisdictions may limit generalizability, and the use of quarterly data might not capture more frequent distress dynamics. Macroeconomic factors were not considered. Contribution: This study offers practical insights for managers and regulators by identifying the key determinants of distress. Theoretically, this study validates the Financial Distress Theory and related frameworks within the unique context of Islamic finance.